Carbonic anhydrase 2 mediates anti-obesity effects of black tea as thermogenic activator - Peng Ma; Jie Xiao; Biyu Hou; Ping He; Xinyu Yang; Yisa Wang; Zijing Wang; Tianshu Xu; Xiuying Yang; Xuan Zhu; Shasha Xiang; Song Li; et al. (Food Science and Human Wellness)
Obesity is a metabolic disorder due to over-accumulation of adipose tissue and ultimately becomes a “disease”. Brown adipose tissue (BAT) thermogenesis and white adipose tissue (WAT) browning emerge as a potential strategy of anti-obesity by dissipating energy as heat. However, drugs based on adipose tissue thermogenesis have not been successfully approved yet. In current study, we found that black tea extract (BTE) obtained by patent-authorized manufacturing process prevented body weight gain as novel thermogenic activator with reduction of adiposity, improvement of adipose distribution, and glucose metabolism improvement in diet-induced obesity mice. Mechanismly, anti-obesity effect of BTE depends on promoting BAT thermogenesis and WAT browning with upregulation of uncoupling protein 1 (UCP1), especially visceral adipose tissue (VAT) with browning resistance. Specifically, utilizing in silico approach of network pharmacology and molecular docking, we identified carbonic anhydrase 2 (CA2) in nitrogen metabolism as anti-obesity target of BTE and further elucidated that protein kinase B (AKT) signaling pathway linked CA2 and UCP1. Meanwhile gut microbiota regulation may prompt the CA2-dependent thermogenesis activation. Our findings demonstrated anti-obesity effect of BTE as thermogenic activator through CA2-mediated BAT thermogenesis and WAT browning via CA2-AKT-UCP1 signaling pathway, which could be developed as promising anti-obesity agent with good safety and efficacy.